KAJI KOMPARASI PEMBANGKIT ENERGI LISTRIK MEMANFAATKAN PENYERAPAN PANAS ASPAL JALAN MENGGUNAKAN TEKNOLOGI TERMOELEKTRIK GENERATOR (TEG) DENGAN PELAT PENYERAP LOGAM DENGAN KEDALAMAN BERBEDA - Wyra Maulana (Jurnal Sains dan Teknologi, 2022)
This study compares the electric power generated by Thermoelectric Generators on three different types of absorbent plates made from metal. The three types of metals are Copper, Aluminum, and Steel. Solar radiation is used to produce electrical energy by using a thermoelectric generator. A thermoelectric generator is a device that converts heat (temperature difference) into electrical energy through the feedback effect. The module used is Thermoelectric type SP 1848. Asphalt is the type of AC-WC with a size of 300 mm x 300 mm x 100 mm. The three plates varied in depth from 2 cm, 4 cm, and 6 cm. At a plate depth of 2 cm, the maximum power for Copper that can be produced is 0.034 W when solar radiation is 887 W / m2. On Copper plates, the total energy is 0.048 W at 2 cm depth. Leaves with a depth of 2 cm are considered better because they produce greater power than plates of 4 cm and 6 cm depth.